BIOADSORPSI Fe(II) OLEH KULIT BUAH JERUK Citrus nobilis Lour. var microcarpa TERMODIFIKASI Ca(OH)2 - Norvi Fatmawati; Thamrin Usman; Titin Anita Zahara (Indonesian Journal of Pure and Applied Chemistry, 2018)
Pontianak peel fruit waste contains pectin, cellulose, and hemicellulose which can be used as heavy metal adsorbents by modifying using Ca(OH)2. The purpose of this study was to determine the physicochemical characteristics of calcium-modified Pontianak Citrus adsorbents (JeP-Oca), determine the maximum capacity of Fe(II) adsorption by JeP-OCa, and JeP-OCa adsorption kinetics. The characteristics of the adsorbent were analyzed using the Fourier Transformation Infra Red (FTIR) showing the functional groups of –OH and -COOH, Electron Scanning (SEM) Microscopy showing the surface structure of the canal and many irregular niches. The adsorption isotherm method with the BET model showed a large difference in porous surface area, namely 104.872 m2/g for JeP, 242.649 m2/g for JeP-ONa and 3759.745 m2/g for JeP-OCa. Optimization of the influence of pH, adsorbent mass, adsorbate concentration, and time using the column method. Adsorption isotherm followed the Freundlich isotherm model with maximum adsorption capacity value of 22.7272 mg/g. Fulfill the pseudo-order 2 reaction kinetics with a rate constant value of 4.097 L/mg. Min. The adsorption application using groundwater resulted in absorption efficiency of 82.99%.